EVALUATING THE IMPACT OF DENSITY ON ACCESS TO LOCAL FACILITIES IN URBAN NEIGHBOURHOODS - Wan Mohd Rani, Wan Nurul Mardiah (PLANNING MALAYSIA, 2014)
Local services and facilities in residential neighbourhoods play an important role towards the social sustainability of local residents. It is believed that having good provision and access to these local services and facilities would contribute significantly to the quality of life and residents’ well-being. The form of the neighbourhood influences the way people live in the neighbourhood. The way people settle in neighbourhood’s shapes the quality of life, the richness of the local economy, the level of social cohesion, the level of safety and the amount and the kind of human activities in public spaces. Different urban forms can have very different degrees of sustainability. Density is one of the urban form elements that have been research numerous times and proven to have an influence on the neighbourhood sustainability. Density is the most easily measured urban form element either at a macro level (city) or micro level (neighbourhood). This research discusses the impact of density on the micro scale through estimating its influence on access to local facilities. Through the use of household survey and supported by observation survey, this study findings on the impact of density on access and use of local facilities. The study concludes with establishing the findings of the survey to reflect and fit into the body of knowledge and how it would improve the guidelines and policy on social sustainability in improving the urban living as a whole.